Exploring genetic diversity in Oryza glaberrima for improved nitrogen recycling and high-temperature tolerance - Ahammed, Md Tanvir (2024)
The production of rice is projected to decline because of the increase in global temperatures. Developing climate-resilient rice varieties is an urgent necessity to guarantee food security in the future. It is crucial to understand the genetic foundation and molecular mechanisms of plant responses to high temperatures to improve their heat stress tolerance through genetic manipulation. Although many studies have focused on improving rice heat tolerance through genetic engineering, few studies have focused on identifying heat-tolerant traits from natural variations. African rice (Oryza glaberrima) evolved separately from Asian rice (Oryza sativa) and poses an important source of natural variations for abiotic stress resilience. The research described here used 155 accessions of O. glaberrima to investigate different heat-responsive traits and identify heat-tolerant accessions. This research also endeavoured to dissect transcriptomic responses to high temperatures in these accessions.